Isolation, Identification and Antibacterial Testing, Indigenous Bacteria from Apis Mellifera's Honeycomb North Sumatra Origin - Esibrena Br Kemit; Yermia S. Mokosuli; Helen J Lawalata (Jurnal Biologi Tropis, 2022)
Honeycomb can be used as a source of antibacterial, this is due to the content of secondary metabolites in the form of flavonoids in the honeycomb which serves as a protective determinant of honey quality. This study aims to isolate, identify and test antibacterial isolates of Indigenous bacteria from Apis mellifera nests against gram-positive bacteria S. aureus and gram-negative bacteria E. coli. This research used descriptive method and the research data were obtained through laboratory experiments. The results of the isolation stage of indigenous bacteria obtained seven (7) isolates AM1, AM2, AM3, AM4, AM5, AM6, AM7 Indigenous bacteria from Apis mellifera bee hives. AM1 and AM4 isolates were similar to the Enterobacter genus, AM2 isolates to Corynebacterium genus, AM3 and AM6 isolates to Paracoccus genus, and AM5 and AM7 isolates to Azotobacter Sp. The seven isolates of Indigenous bacteria have potential as antibacterial and the diameter of the inhibition zone against E. coli bacteria is AM1 (8.88 mm), AM2 (8.65 mm), AM3 (8.03 mm), AM4 (6.41 mm) , AM5 (9.07 mm), AM6 (9.53 mm) and AM7 (9.44 mm) while against S. aureus AM1 (9.08 mm), AM2 (9.23 mm), AM3 (9.15 mm), AM4 (8.70 mm), AM5 (10.44 mm), AM6 (11.56 mm) and AM7 (9.0 mm).